Evaluation of serological responses in horses challenged with Burkholderia pseudomallei using current diagnostic tests for glanders - Wernery, Ulrich; Rodriguez Caveney, Marina; Wernery, Renate; Raghavan, Rekha; Laroucau, Karine; Syriac, Ginu; Thomas, Shruti Miriam; John, Jeeba; Joseph, Marina; Jose, Shantymol; Joseph, Sunitha; Woo, Patrick (Veterinaria Italiana, 2019)
Six horses were challenged experimentally with a strain of Burkholderia pseudomallei isolated from a fatal case of the infection in a dromedary camel years earlier in the Emirate of Dubai. Three horses were inoculated subcutaneously and in 3 the bacterium was administered by the oral route. Four of the horses became serologically positive based on reactions to one or more of the OIE described tests for glanders. B. pseudomallei was re-isolated from the 4 serological positive horses. Only one of the subcutaneously infected horses, developed fever for 3 days. The white blood cell values and the neutrophil counts were also elevated. The study confirmed that existing serological test for diagnosing glanders cannot differentiate between glanders and melioidosis in horses.